Seroepidemiological study of cytomegalovirus and associated factors in women working in kindergartens. - García, Javier (2015)
To determine the seroprevalence of cytomegalovirus in women of childbearing age who work in kindergartens of Lima, identify those capable of acquiring a primary infection (HIV-negative) and factors associated with seroprevalence of cytomegalovirus in this risk group. DESIGN: A total of nine kindergartens who met the eligibility criteria, with a total of 79 women of childbearing age were included. The information was gathered from questionnaires. All women underwent including the AxSYM CMV 1gG to detect antibodies against cytomegalovirus 1gG. The information collected was processed using frequency analysis and to determine the association contingency coefficient (C) and chi-square test for significance was calculated. RESULTS: The seroprevalence (serology) was found 72.1%, what determines a percentage susceptibility of 27.8% (22 subjects). The associated seropsitividad moderate and statistically significant (p <0.05) with low socioeconomic status and changing diapers in three or more times a week. A nonsignificant weak association, but, between seropositivity and working in kindergartens for more than two years was found. Concussion: In the study population there is a high rate of cytomegalovirus seropositivity, associated with socioeconomic status and changing diapers.